Komparasi Destination Branding dalam Official Website Negara Singapura-Malaysia-Indonesia - Sutanto, Ryan Pratama; Natadjaja, Listia; ., Erandaru (Nirmana, 2010)
High profit income has attracted South Asian countries to compete in the fields of tourism marketing. Destination branding as a differentiating factor is an alternative approach in marketing communication. The purpose of this research is to make a comparison study of destination branding application in Singapore's, Malaysia's and Indonesia's tourism official websites. Destination branding in websites as part of promotion campaigns is a strategy used by each country to promote tourism to consumers worldwide. This research uses qualitative method, and involves experts in the fields of Information Technology (IT) and Visual Communication Design. Each website's elements contributes in the success of a country's destination branding and influences its brand image.